FEATURES OF THE ARCHITECTURE FOR INTERNET COMMERCIAL CONTENT MANAGEMENT SYSTEM BASED ON METHODS OF MACHINE LEARNING, WEB MINING AND SEO TECHNOLOGIES - Vysotska, V.; Demchuk, A.; Lytvyn, V. (Radio Electronics, Computer Science, Control, 2019)
Context. Today, most corporations are constantly rethinking business from the point of view of the Internet, namely its availability, broad reach and ever-changing needs of the user. The e-commerce web-site, which provides user-friendly experience, including the ability to quickly find the products that are necessary for its portables and taste, is more in favor of competitive advantage. Objective of the study is to develop a general architecture of the intellectual system for the distribution of commercial content in the Internet space, based on the study of the neural network in accordance with the history of the psychedelic region to provide unique content using the approach of personalization and the use of tags. Method. The model of information system of commercial content personalization for the user needs is developed. Also the method of distributing commercial content based on the approach of personalization and the tags use is developed. In this case, the neural network training is used to create a recommendation tag and marketable personalization tools. The customization algorithm allows you to associate each user with a list of products that they are most likely to be interested in, and can predict what customers might want to see even if they do not yet know about it. The developed method can be used to provide a more relevant set of content. Also, the developed method gives the opportunity to classify the relevant content or show it earlier in the process of rolling the pages to avoid consumers choosing the wrong content or spending time scrolling when looking for a product. Results. The developed system is intended for distribution of information technology products (publications, books, courses, videos, files, etc.) through the Internet. Conclusions. Implementation of this system will allow access to certain types of content to the general public, since the site will be placed on the World Wide Web; on the other hand, another part of the purpose of creating this system is a commercial component, namely, the receipt of profits by the owner or administrator of the intellectual system, through the mechanisms of e- commerce.